Environmental risk factors of the mortality of COVID-19 in Shiraz: Distributed lag nonlinear model - Adibian, Morteza; Alavi Majd, Hamid; Namdari, Mahshid; Khatamifar, Vahid; Khodakarim, Soheila (Archives of Advances in Biosciences, 2024)
Introduction: COVID-19 is an infectious disease first reported in Wuhan, China on December 31, 2019. Environmental factors are considered important risk factors due to the infectiousness of the disease of COVID-19. The purpose of this study is to investigate the environmental risk factors of COVID-19 in Shiraz, Iran. Materials and Methods: This study is based on daily scale data of COVID-19 disease cases and environmental variables from February 2020 to December 2022, using a distributed lag nonlinear model (DLNM) with a zero-inflated Poisson (ZIP) link function to assess the nonlinear and lag effects of temperature on the death of COVID-19. Results: The average daily deaths were 2.2±2.3. A significant effect was reported between temperature and its delays, the number of hospitalized patients, and the spatial-temporal effects on the number of daily deaths due to the COVID-19 disease. The effect of average wind speed was not statistically significant. Conclusion: The findings of the present study showed the negative effect of high temperatures on increasing the number of deaths within the next two weeks. This effect can be assigned to the increase in people's movements in pleasant weather. Therefore, it is necessary to control the movement of people when the weather is pleasant.